A Review of Policies and Practices in Science, Technology, and Innovation Development in China and India: Implications for Vietnam - Minh Quan, Dao (VNU Journal of Science: Policy and Management Studies, 2025)
In the context of globalization and the rapid advancement of science, technology, and innovation (STI), China and India have implemented strategic policies to enhance domestic capabilities and strengthen their national positions. China has focused on building a comprehensive innovation system by implementing policies that support enterprises, scientific research institutions, and the development of cutting-edge technologies such as artificial intelligence, big data, and green technology. China's STI policies are closely aligned with its economic development strategies, creating a favorable environment for technology transfer and the building of innovation capacity. Meanwhile, India emphasizes the development of an STI ecosystem rooted in indigenous knowledge while also encouraging international collaboration. Indian policies prioritize advancements in space technology, biotechnology, renewable energy, and the software industry, while promoting private sector innovation to improve global competitiveness. This study analyzes the STI policies of these two countries, examining both their theoretical underpinnings and practical implementation across different development phases. Furthermore, the paper draws key lessons and offers policy recommendations for Vietnam, particularly in developing an effective STI policy framework, fostering innovative enterprises, and strengthening applied research capacity.